In-vitro evaluation of the effects of insertion and sterilization procedures on the mechanical and surface characteristics of mini screws - Civan Aved Hergel; Yasemin Bahar Acar; Mustafa Ateş; Nazan Küçükkeleş (Istanbul University, 2019)
Purpose The aim of the present study was to investigate the effects of insertion and sterilization on primary stability and to examine the mechanical and surface characteristics of mini screws. Materials and methods 140 miniscrews (70 Dual-Top; 70 Ortho-Easy) were divided into 3 groups. Group 1: control group, 10 miniscrews of each brand, evaluated without any primary procedure. Group 2: 30 miniscrews of each brand, each inserted into the sawbone once, then sterilized and tested. Group 3: 30 miniscrews of each brand, each inserted into the sawbone twice, sterilized after each insertion and then tested. The miniscrews were evaluated for changes in primary stability, mechanical and surface characteristics with scanning electron microscopy (SEM) analysis, torsion tests, maximum insertion-removal torques and vertical-horizontal pull out strength tests. Results The maximum insertion torque values of the unused miniscrews (Group 1) were found to be significantly higher than those of the reused (Groups 2, 3) mini screws (p<0.05). Removal torque, vertical-horizontal pull-out strength and torsional strength value changes were found to be statistically insignificant. In SEM analysis, wear and atrophy were seen on the threads of used miniscrews especially in the apical region and the oxide layer was seen to have disappeared from some regions of the coated miniscrews. Conclusion Although wear and atrophy were detected in SEM analysis of used miniscrews, the overall primary stability and fracture torque resistance tests did not show any significant changes after the first and second insertion and sterilization procedures.